THE EFFECT OF POST-HARVEST HANDLING PRACTICES ON THE QUALITY AND MARKETABILITY OF HARVESTED ONIONS IN JERE LOCAL GOVERNMENT AREA, BORNO STATE, NIGERIA - Bulama, Y. M.; Idi, A. S.; Kyari, M. B.; Abuna, A. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
This study examined the effects of post-harvest handling practices on the quality and marketability of onion in Jere Local Government Area. A total of 40 respondents who are into onion storage were selected for the study using a multi-stage sampling approach. A structured questionnaire served as the main instrument for the primary data was used while secondary data were also obtained. The analysis of the socio-economic characteristics revealed that; majority of the respondents (57.5%) fall within the age group of 36 - 45 years, emphasizing the predominance of economically active traders with an average age of 36.4 years. About 95% of respondents are males, reflecting a significant gender disparity in the onion storage sector. While education levels vary, a significant portion of respondents possess some formal education with majority 47.5% of respondents had non-formal education, this diversity highlights the potential influence of education on storage strategies and income diversification. The study reveals that most respondents (57.5%) have been involved in onion storage for 1 - 5 years, with an average of 6 years, indicating relatively low levels of experience. Challenges such as limited resources, traditional practices, and cultural factors contribute to this lack of experience. Traditional storage structures are the predominant choice, with 90% of respondents utilizing them, accompanied by a strong preference for woven sacks as packaging materials for onion storage due to their protective attributes. Various methods are employed to preserve onion freshness during storage, including floor spreading, enhanced ventilation, utilization of local stores, and other techniques. Statistical analysis reveals that onion size, proper storage, colour and firmness are found to positively influence quality of onion. Stocking size, price, packaging materials, experience and duration are found to positively influence marketability of onion. Moreover, the study underscores overwhelming support with majority 95% of respondents that support the adoption of improved post-harvest handling practices to reduce spoilage and elevate onion quality. The study concludes that the onion marketers practice on a small scale by storing onions in smaller quantity in traditional structures, using woven sacks for packaging. Size of onion, color, firmness significantly influences onion quality. Stocking size, quantity, duration significantly influence onion marketability. While the major constraints include poor handling, inadequate storage facilities and pest infestation. Key words: Post-harvest handling practices, onion, quality, marketability, Jere LGA, Borno.